Governance, Risk, and Compliance (GRC), Dividend Policy, and Debt Policy as Accentuation of Firm Value in The Banking Financial Service Sector - Siwi, Puput Ranu; Hanifah, Umi; Suhatmi, Erna Chotidjah (IAIN Kudus, 2023)
Abstract : Increasingly high business competition requires companies to maintain a competitive advantage to be able to maintain the value of the company. This study aims to analyze the effect of governance, risk, and compliance (GRC), dividend policy, and debt policy on firm value in conventional banking companies listed on the IDX in 2017-2021. This research is quantitative. Data analysis techniques used descriptive statistical analysis, classical assumption tests, and hypothesis testing. The results show that managerial ownership, credit risk, independent board of commissioners, and dividend policy do not affect firm value. Institutional ownership, liquidity risk, and debt policy affect firm value. Managerial ownership, institutional ownership, credit risk, liquidity risk, independent board of commissioners,Keywords : Governance, Risk, and Compliance (GRC), Dividend Policy, Debt Policy, Firm Value.